Analisis Laporan Keuangan BMT Amanah Ummah Studi atas Kesesuaian PSAK No. 59 - Rifai, Ahmad, Dr. Supawi Pawenang, MM (2016)
One of the functions of accounting at Bank and Non Bank Financial Institutions is to know the financial information contained in the convensional company. But in sharia accounting, there is a fundamental difference from the convensional one in their objectives. The purpose of sharia accounting is not only for the interests of company or individual alone but to have responsibility aspect to Allah SWT, as well. It's rules are based on the law of God contained in the Qur'an and Hadith. The purpose of this study is to determine the suitability of financial statements of BMT Amanah ummah with SFAS No. 59 on Accounting for Islamic Banking. Specifically regarding the financial statements and the financial statements Balance Sheet Income of BMT Amanah Ummah. To find out the problem, researcher used field research approach. The method used in this research is descriptive-qualitative method which is a method of describing the incident or the facts in the empiric, in this case BMT Amanah Ummah. By comparing and analyzing the accounting reports of BMT Amanah Ummah and it's conformity with SFAS No. 59 which are supported by interview, documentation, and observation. From this study, based on the recognition and measurement, it can be concluded that presentation and disclosure of financial accounting transaction implementation of various financing institutions of BMT Amanah Ummah products in which includes specific contract in its reporting, are in accordance with SFAS No. 59, and the system used by BMT Amanah Ummah in the input transaction data from it's existing contract, using special computerized accounting software in accordance with SFAS No. 59 so automatically in financial reporting, both it's financial statements Balance Sheet and Profit and Loss of financial statements are in accordance with SFAS No. 59 on Accounting for Islamic Banking, including the accounts in the Balance Sheet and Profit and Loss therein are in accordance with SFAS No. 59.